Efficacy and Safety of Nicotine Replacement Therapy in Intensive Care Units: A Systematic Review - Mohammed Kanan (Asian Journal of Pharmaceutics (AJP), 2024)
Nicotine replacement therapy (NRT) is a potential intervention for managing nicotine withdrawal symptoms in critically ill patients in the intensive care unit (ICU). This systematic review evaluated the effectiveness and safety of NRT in adult ICU patients with a history of nicotine dependence or tobacco use. A comprehensive literature search was conducted from January 31, 2010, to September 31, 2024, using the PubMed, Scopus, and Web of Science databases. Eight studies that assessed the impact of NRT on nicotine withdrawal symptoms, ICU stay duration, delirium incidence, mortality, and adverse events were included in the review. These results suggest that NRT may be effective in reducing nicotine withdrawal symptoms in patients in the ICU. However, evidence regarding its impact on ICU outcomes, such as length of stay and delirium incidence, is inconclusive. Some studies reported potential adverse effects, including increased agitation and delirium, whereas others found no significant increase in adverse events. The safety profile of NRT in the ICU setting remains controversial, and further, highquality randomized controlled trials are required to establish its efficacy and safety in critically ill patients. This review highlights the importance of individualized patient management and the needs for a balanced approach when incorporating NRT into ICU care, considering factors such as nicotine dependence severity, cardiovascular health, and the overall clinical profile. Future research should focus on optimizing NRT use in the ICU, exploring optimal formulations and dosages, and investigating the potential interactions with common ICU medications.